Something's wrong at my house children in domestic violence - Queensland. Department of Family Services (Brisbane, Qld. : Dept. of Family Services, 1989)
Designed to create awareness about the effects of domestic violence on children. Shows enacted scenes and the real life experiences of survivors.
Pamphlet titled: The Domestic Violence (Family Protection) Act 1989.
Recommended for mature audiences 15 years and over.
Keywords: Family violence